2013
DOI: 10.1073/pnas.1217780110
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of glycoprotein C from Rift Valley fever virus

Abstract: Rift Valley fever virus (RVFV), like many other Bunyaviridae family members, is an emerging human and animal pathogen. Bunyaviruses have an outer lipid envelope bearing two glycoproteins, G N and G C , required for cell entry. Bunyaviruses deliver their genome into the host-cell cytoplasm by fusing their envelope with an endosomal membrane. The molecular mechanism of this key entry step is unknown. The crystal structure of RVFV G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
186
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(195 citation statements)
references
References 45 publications
7
186
1
1
Order By: Relevance
“…Similar to that observed for the Gc glycoprotein from the related RVFV Gc (17), SFTSV Gc eluted as a single monomeric species on size exclusion (SEC) at neutral pH (8.0). Upon acidification (5.0), we observed a mixture of monomeric and putative trimeric species, consistent with rearrangements of the molecule to a postfusion state ( Fig.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Similar to that observed for the Gc glycoprotein from the related RVFV Gc (17), SFTSV Gc eluted as a single monomeric species on size exclusion (SEC) at neutral pH (8.0). Upon acidification (5.0), we observed a mixture of monomeric and putative trimeric species, consistent with rearrangements of the molecule to a postfusion state ( Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Interestingly, SFTSV is also capable of cell entry via extracellular vesicles, which likely allows evasion of the host immune system (16). Structural studies of the cognate Gc from RVFV (17) in the prefusion conformation revealed that the phleboviral Gc forms a class II architecture, which has been also observed for envelope glycoproteins from positive-sense RNA viruses from the Togaviridae and Flaviridae families (18,19). A similar class II architecture has also been observed in cell-cell fusion proteins, although the mechanism of membrane fusion is likely to differ from viral fusion as evident by the absence of a hydrophobic fusion loop (20).…”
mentioning
confidence: 96%
“…Histidine side chains have pK a values in the range of 6-6.4 and therefore typically become protonated during endosomal acidification. The increase in positive charge resulting from histidine protonation is an important part of the pH sensing mechanism of many viruses (24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…Bunyavirus particles are enveloped with glycoproteins that form the spike-like surface responsible for attachment to host cells. Gn of Rift Valley fever virus forms a capsomer protruding from the virions and might retain receptor binding activity (7), while Gc of hantaviruses, Rift Valley fever virus, and other members of the Bunyaviridae family is believed to be a class II viral fusion protein responsible for viral fusion (8)(9)(10). Bunyaviruses invade host cells by interacting with cellular receptors (11); however, little is known about receptors and host factors for most bunyaviruses.…”
mentioning
confidence: 99%